Museum of failure - Ellen Harvey - Hall, Emily ca. 20. Jh (Miller, 2015)
Harveys latest major work combines the interests and forms of her recent projects. The ongoing Museum of Failure (2007 )a new elaboration of which is part of the Biennialincludes Collection of Impossible Subjects, a rear-illuminated plexiglass mirror wall hand-engraved with a salon-style exhibition of ornately framed, sandedout rectangles. Visible through an opening in one of them is Invisible Self-Portrait in My Studio, a painting of an identical collection of frames, except that these hold paintings based on photographs the artist took of herself in a mirror where the image is obliterated by the cameras flash. It is a nuanced twin bill that probes conventional wisdom about the artist and the museum, about making and seeing
Includes bibliographical references
Keywords: Harvey, Ellen 1967- / Criticism and interpretation / Harvey, Ellen 1967- / Criticism, interpretation, etc; Harvey, Ellen -- 1967-; Malerei; Bildband